Legal Construction of Electronic Money-Based Sale Contracts in The Perspective of Contemporary Islamic Commercial Jurisprudence - Orin Oktasari; Agnes Yolanda; Gustiya Sunarti (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The rapid growth of digital payment systems has significantly transformed contemporary economic transactions, particularly through the widespread adoption of electronic money (e-money). While electronic money offers efficiency, convenience, and financial inclusion, its legal characterization within Islamic commercial jurisprudence remains a subject of scholarly debate. This study aims to analyze the legal construction of electronic money-based sale contracts from the perspective of contemporary Islamic commercial jurisprudence (fiqh al-mu'amalat al-mu'ashirah). Specifically, the study examines the contractual relationships among users, issuers, merchants, and payment service providers and evaluates their conformity with Islamic legal principles and the objectives of Sharia (maqasid al-shariah). This research employs a qualitative library research method using a normative and conceptual approach. Data were collected from classical and contemporary Islamic jurisprudential literature, peer-reviewed journal articles, regulations issued by Bank Indonesia and the Financial Services Authority (OJK), DSN-MUI fatwas, and other relevant scholarly sources. The collected data were analyzed through qualitative content analysis and comparative fiqh approaches. The findings reveal that electronic money transactions cannot be adequately explained through a single contractual framework. Instead, they constitute a hybrid contract (al-'uqud al-murakkabah) involving multiple interconnected contracts. The relationship between users and issuers is primarily characterized as qardh, although certain elements of wadiah remain relevant. The relationship between users and merchants is governed by a bai' (sale and purchase) contract, while the relationships involving payment service providers reflect wakalah bil ujrah and ijarah contracts. Furthermore, electronic money supports the objectives of maqasid al-shariah, particularly hifz al-mal (protection of wealth), by enhancing transaction efficiency, security, and financial accessibility. This study contributes a comprehensive legal construction model for electronic money transactions and provides a theoretical foundation for the development of Sharia-compliant digital payment systems in the contemporary financial landscape.